The radius of starlikeness of the certain classes of p-valent functions defined by multiplier transformations - Acu, Mugur; YAVUZ, EMEL; POLATOĞLU, YAŞAR (Springer International Publishing, 2008)
The aim of this paper is to give the radius of starlikeness of the certain classes of Open image in new window-valent functions defined by multiplier transformations. The results are obtained by using techniques of Robertson (1953,1963) which was used by Bernardi (1970), Libera (1971), Livingstone (1966), and Goel (1972).
Keywords: Full Article; Publisher Note